Karakteristik Akad Mukhabarah bil Mudharabah Pada Kemitraan Pertanian Tebu - Auliya Safira Putri; Dyah Ochtorina Susanti; Rahmadi Indra Tektona (University of Udayana, 2023)
The presence of an imbalance in the partnership between sugar mills and sugarcane farmers under the agricultural land leasing system has an impact on national sugar productivity. This study was based on the speculative hypothesis that existing partnerships frequently harm sugarcane farmers. The goal of this study is to examine a type of partnership that occurs in sugar cane farming in Indonesia using a new method based on sharia economic law known as the mukharabah bil mudharabah contract. The research method employed in this study is normative-juridical, including statutory and conceptual methods. This research yielded findings in the form of a new concept that depicts the characteristics of sugarcane farmer partnerships based on the mukharabah bil mudharabah contract and provides policy input for the government regarding sugarcane farmer partnerships with financing institutions based on the mukharabah bil mudharabah contract. In relation to this, the researchers proposed the concept of a